The Academic Nature of the City and Its Market Potential on the Example of Szczecin - Karina TESSAR (Communications of International Proceedings, 2021)
The article is an attempt to show the usefulness of the part of the academic community, which are the students, in the development of a territorial unit. Students of "Tourism and recreation" at the University of Szczecin assessed the territorial sub-products of Szczecin, pointing to their market potential, the factors that constitute a development difficulty or barrier, as well as the marketing activities which could be helpful in solving problems. The respondents' opinions clearly show that they see development potential in each of the analysed territorial sub-products of Szczecin. As a homogeneous group, they acted as experts whose knowledge and ideas may be of interest to city planners, people and organizations which care about the development of Szczecin as an academic centre. Academic development is one of the city-forming factors, and one of the priorities in Szczecin's development strategy until 2025. Data from the respondent surveys was collected for 5 years. A literature review, foresight research, expert interviews, as well as discussion, were also used. Research has shown that the development of a knowledge-based economy is important for raising the standard of living in the city, and last year students have this knowledge that can be useful.
Keywords: Territorial Marketing; Academic Community; Tourism And Recreation; Szczecin; Market Potential